Structure and wiring board

By forming a conductor layer on the surface of the insulator, the conductor layer components enter the gap between the insulator and the filler, the problem of conductor circuit peeling caused by the large surface roughness of the insulator layer and the problem of increasing high-frequency transmission loss is solved, and the insulator and conductor layer are realized Excellent adhesion and high precision.

CN119452740APending Publication Date: 2025-02-14TAIYO HOLDINGS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380050317.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, the surface roughness of the surface of the insulating layer is large, which leads to erosion of the conductor circuit in the etching liquid, causing the problem of peeling the conductor circuit. At the same time, the transmission loss of high-frequency signals increases, and the thinning of the insulating layer faces surface roughness. Influence.

Method used

By forming a conductor layer on the surface of the insulator, the conductor layer components enter the gap between the insulator and the filler, forming a thin film covering a plurality of fillers, reducing the surface roughness of the insulator surface, and improving the adhesion between the insulator and the conductor layer.

Benefits of technology

It realizes the reduction of the surface roughness of the insulating layer and improves the adhesion between the conductor layer and the insulator, and is suitable for high-fine conductor circuit pattern formation and high-frequency power transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119452740A_ABST
    Figure CN119452740A_ABST
Patent Text Reader

Abstract

Provided is a structure which has excellent adhesion and is provided with a conductor layer and an insulator. According to one embodiment of the present invention, a structure (30) is provided with an insulator (10) and a conductor layer (20). The conductor layer (20) is provided on at least a part of the surface of the insulator (10). The insulator 10 contains a resin 12 and a filler 14. A conductor layer component identical to at least one component constituting the conductor layer (20) enters between a part of the filler (14) and the resin (12) from an interface (16) between the insulator (10) and the conductor layer (20), and is connected to the conductor layer (20).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a structural body and a wiring board. Background Art

[0002] Wiring boards are mostly used in electronic devices. As a method for manufacturing such wiring boards, for example, a multilayer technology of the following lamination method is known: prepreg and copper foil are pressed, and insulating layers and conductor layers are alternately stacked on an inner circuit board (so-called copper-clad laminate) formed with a circuit. Patent Documents 1 and 2 propose the following method: an epoxy resin composition is applied to an inner circuit board formed with a circuit, and after heating and curing to form an insulating layer, the surface of the insulating layer is roughened with a roughening agent to form a concave-convex shape, and a conductor layer (circuit) is formed by chemical plating and electrolytic plating.

[0003] In addition, Patent Document 3 proposes a method for manufacturing a multilayer printed circuit board, in which an adhesive sheet formed of an epoxy resin composition is laminated on an inner layer circuit board having a circuit, and after being heated and cured to form an insulating layer, the surface of the insulating layer is roughened into a concave-convex shape with a roughening agent, and a conductor layer is formed by chemical plating and electrolytic plating.

[0004] The above-mentioned techniques all improve the adhesion between the conductor layer and the insulator by roughening the surface of the insulator.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 7-304931

[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 7-304933

[0009] Patent Document 3: Japanese Patent Application Laid-Open No. 11-87927 Summary of the invention

[0010] Problem that the invention aims to solve

[0011] In the pattern formation (patterning) of the conductor circuit in the stacking method, the unnecessary conductor layer is removed by etching liquid. At this time, in the above-mentioned technology, the surface of the insulating layer has large unevenness (surface roughness), so the etching liquid corrodes the bottom of the conductor circuit from the concave part, thereby causing the problem of the conductor circuit peeling off. Furthermore, in the pattern formation of high-precision conductor circuits in recent years, the contact area between the conductor circuit and the insulating layer is small, so the above-mentioned problem tends to be significant. In addition, recently, with the high frequency of electrical signals, research has also been conducted on reducing transmission loss. The transmission loss increases in proportion to the contact area between the conductor circuit and the insulating layer. Therefore, from this point of view, it is also required to reduce the surface roughness of the insulating layer surface.

[0012] Furthermore, as the number of layers of multilayer printed wiring boards increases and they become lighter and thinner, research on thinning the insulating layer is also being promoted. The insulating layer ensures a constant thickness to ensure electrical insulation in the thickness direction, but when the surface roughness of the insulating layer is large, there is also a problem that the thickness of the layer only increases the height of the surface unevenness.

[0013] As described above, in order to obtain a thinner, more precise, and more functional wiring board, a technology for reducing the surface roughness of the insulating layer and achieving excellent adhesion with the conductor circuit is required.

[0014] Therefore, an object of the present invention is to provide a structure in which the surface roughness of the insulator surface is reduced and the adhesion between the insulator and the conductor layer is excellent.

[0015] Solutions for solving problems

[0016] The present inventors have found that the above-mentioned problems can be solved by forming an insulator and a conductor layer formed on the surface thereof into a specific structure that is not expected in conventional wiring boards, and have completed the present invention.

[0017] That is, according to a first aspect of the present invention, there is provided a structure, characterized in that it comprises:

[0018] Insulators, and

[0019] a conductive layer provided on at least a portion of the surface of the insulator,

[0020] The insulator comprises a resin and a filler.

[0021] The conductive layer component which is the same as at least one component constituting the conductive layer enters from the interface between the insulator and the conductive layer into between a part of the filler and the resin, and is connected to the conductive layer.

[0022] In the first aspect, the conductive layer component that enters between the filler and the resin can form a thin film covering the plurality of fillers.

[0023] In the first embodiment, the average particle size of the filler may be 1.0 μm or less.

[0024] In the first aspect, the depth of the conductive layer component that enters between the filler and the resin from the interface may be 1.5 times or more and 22 times or less the average particle size of the filler.

[0025] In the aforementioned first embodiment, the filler may be a metal oxide.

[0026] In the aforementioned first embodiment, the component may be a metal component.

[0027] A second aspect of the present invention is a wiring board having the structure of the first aspect.

[0028] Effects of the Invention

[0029] According to the present invention, it is possible to provide a structure in which the surface roughness of the insulator surface is extremely small and the adhesion between the insulator and the conductor layer is excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a schematic cross-sectional view schematically showing one embodiment of the structure of the present embodiment.

[0031] Figure 2 This is a schematic process diagram of the structure of this embodiment.

[0032] Figure 3 This is an enlarged image of the cross-sectional photograph of the structure of Example 3.

[0033] Figure 4 This is an enlarged image of the cross-sectional photograph of the structure of Example 6.

[0034] Figure 5 This is an enlarged image of the cross-sectional photograph of the structure of Comparative Example 2. DETAILED DESCRIPTION

[0035] Hereinafter, the present invention will be described in detail.

[0036] In the present invention, International Publication No. 2020 / 017570 as a related application is cited by appropriate reference.

[0037] In the present invention, "surface" refers to the boundary surface between the insulator and the gas phase, and does not include the boundary surface in the gap formed by the gap forming process described later. In addition, in the present invention, "interface" refers to the boundary surface between the insulator and the conductor layer, and is set to be the surface of the gap portion into which the conductor layer component is inserted.

[0038] When a plurality of upper limits and a plurality of lower limits are described below, all numerical ranges that can be set by freely combining these upper limits and lower limits are described.

[0039] Hereinafter, in the present specification, the expression "a to b" in the description of the numerical range means a or more and b or less unless otherwise specified.

[0040] Hereinafter, unless otherwise specified, various measurements are performed with the ambient temperature being room temperature (eg, 25° C.).

[0041] Hereinafter, unless otherwise specified, the content, compounding amount, etc. of each component indicate the amount based on components other than volatile components (also referred to as non-volatile components, solid components).

[0042] When a certain compound is described below, its isomers are also described.

[0043] Hereinafter, "(meth)acrylic acid" means including both "acrylic acid" and "methacrylic acid". In addition, "(meth)acrylate" means including both "acrylate" and "methacrylate".

[0044] In the present invention, phenols used as a raw material of a polyphenylene ether resin (PPE) and capable of becoming a structural unit of the polyphenylene ether resin are collectively referred to as "raw material phenols".

[0045] Hereinafter, the structure of the present embodiment will be described, and then a method for producing the structure of the present embodiment and a method for using the structure of the present embodiment will be described in sequence.

[0046] <<<Structure>>>

[0047] The structure of the present embodiment is described in detail with reference to the accompanying drawings. In the drawings referred to below, the same symbols are used to represent components having substantially the same functions, and their descriptions are sometimes omitted. It should be noted that the dimensional ratios of the drawings cited in the following embodiments are exaggerated for the sake of convenience of explanation and are sometimes different from the actual ratios. In addition, the drawings cited in the following embodiments are simplified or schematically represented for the sake of convenience of explanation, and some of the components are omitted.

[0048] Figure 1 1 is a schematic cross-sectional view schematically showing an embodiment of a structure of the present embodiment. The structure 30 of the present embodiment includes an insulator 10 and a conductor layer 20. Furthermore, the conductor layer 20 is provided on at least a portion of the surface of the insulator 10 ( Figure 1 In the case where the conductor layer 20 is provided, the boundary surface between the insulator 10 and the conductor layer becomes the interface 16). It should be noted that, Figure 1 It is an enlarged cross-sectional view of a portion near the interface 16 between the insulator 10 and the conductor layer 20 in the structure 30 .

[0049] <<Insulator>>

[0050] The insulator 10 of the present embodiment includes a resin 12 and a filler 14. In addition, in the present embodiment, in the depth direction from the interface where at least a portion of the conductor layer is formed in the insulator 10, the conductor layer component is sandwiched between the resin 12 and a portion of the filler 14, and there is a region where the resin 12 and the filler 14 are not in contact. The insulator 10 is typically a cured product formed of a curable composition including various components described in detail below.

[0051] The surface 17 of the insulator 10 of the present embodiment before the conductor layer is provided (the boundary surface with the conductor layer 20 after the conductor layer 20 is provided is referred to as the interface 16; see Figure 2 ) has resistance to the gap forming treatment (so-called roughening treatment) described later, and the change in surface roughness Ra before and after the gap forming treatment is suppressed to an increase of 0 to 100 nm. For example, on a smooth surface with a surface roughness Ra of 40 nm before the gap forming treatment, the surface roughness Ra after the gap forming treatment becomes less than 140 nm. In this way, even if the surface roughness Ra of the surface 17 is not changed, the present embodiment can fully obtain the close adhesion between the insulator 10 and the conductor layer 20, and is therefore suitable as an electronic component for pattern formation of high-precision conductor circuits and high-frequency power transmission (such as 5G communications, etc.).

[0052] It should be noted that in this specification, "surface roughness Ra" refers to the arithmetic mean surface roughness Ra, which can be measured using a white interference microscope (Bruker Contour GT-I, measuring range 0.17mm×0.13mm) or the like. In addition, the surface for measuring the surface roughness Ra of the insulator 10 after the gap forming treatment in this specification may be the surface 17 before the stacked conductor layer 20, or the surface 17 after the stacked conductor layer 20 is removed (wherein, it is limited to the case where the conductor layer 20 is removed under relatively stable conditions (such as ferric chloride solution, cupric chloride solution, and hydrogen peroxide-sulfuric acid etching solution) that at least dissolves the conductor layer 20). The surface roughness Ra of the insulator after the gap forming treatment is preferably less than 140nm, more preferably less than 100nm. The lower limit of the surface roughness Ra of the insulator after the gap forming treatment is not particularly limited, and is 0.1nm, 0.5nm, 1nm, 5nm, etc.

[0053] <<Conductor layer>>

[0054] The conductor layer 20 of the present embodiment is formed of a conductor (metal). The type of the conductor can be appropriately determined according to the type, conductivity, durability, etc. of the insulator 10, and is typically copper or silver. Figure 1 In the embodiment, the conductor layer 20 is a single component, but may include two or more components, or may be a laminate of two or more conductors.

[0055] In the present embodiment, the conductive layer component identical to at least one component constituting the conductive layer 20 enters between at least a portion of the filler 14 and the resin 12, and is connected to the conductive layer 20. In other words, the component of at least a portion of the conductive layer 20 is sandwiched between at least a portion of the filler 14 and the resin 12, forming a thin film 22 connected to the conductive layer 20. In this way, the thin film 22 is the conductive layer component identical to at least one component of the conductive layer 20 as a conductor, and therefore, it can also be said that the thin film 22 is formed by a conductive layer component containing the same conductive component (i.e., metal component) as the conductive layer 20. The thickness of the thin film 22 of the present embodiment is not particularly limited, and is, for example, 100 nm or less. In this way, for the structural body 30 of the present embodiment, the conductive layer component identical to at least one component constituting the conductive layer 20 forms a fine anchor portion in the depth direction from the interface 16 of the insulator 10 with the conductive layer 20, and therefore, the insulator 10 and the conductive layer 20 have excellent adhesion.

[0056] It should be noted that Figure 1 FIG. 1 is a cross-sectional view of the structure 30 of the present embodiment. Therefore, the thin film 22A is not connected to the conductive layer 20 (that is, a portion of the thin film 22 is not connected to the conductive layer 20). Figure 1 The portion of the cross section shown is connected to the conductor layer 20. Whether the conductor layer 20 and the thin film 22 are connected, and whether the thin films 22 are connected to each other, can be confirmed by, for example, a dual-beam scanning electron microscope (FIB-mounted SEM) or the like.

[0057] In the present embodiment, the depth of the conductor layer component entering between the filler 14 and the resin 12 from the interface 16 is preferably 1.5 times or more and 22 times or less, and more preferably 2.0 times or more and 20 times or less of the average particle size (described later) of the filler 14. In the present embodiment, if the depth of the conductor layer component entering between the filler 14 and the resin 12 from the interface 16 is within such a range, sufficient adhesion between the insulator 10 and the conductor layer 20 can be obtained, and both the thin film and electrical insulation of the insulator 10 can be taken into account.

[0058] It should be noted that, in this specification, the “depth from the interface” refers to the longest depth ( 100 Å to 100 Å) of the portion (thin film 22) where the conductor layer 20 component exists, which is perpendicular to the interface 16 toward the insulator 10 (opposite to the conductive layer 20), obtained by taking various cross-sectional photographs of the structure 30 (e.g., a cross-sectional SEM (scanning electron microscope) photograph of the portion where the insulator 10 and the conductive layer 20 are in contact, magnified 5,000 to 100,000 times). Figure 1Specifically, for example, when the average particle size of the filler is 0.1 μm or more, a cross-sectional photograph magnified 10,000 times is obtained, and when the average particle size of the filler is less than 0.1 μm, a cross-sectional photograph magnified 100,000 times is obtained, from which the "depth from the interface" can be calculated. Figure 1 As shown, it is preferred that the conductive layer component that enters between the filler 14 and the resin 12 forms a thin film 22 that covers at least a portion of the filler 14, and it is more preferred that a thin film 22B that covers a plurality of fillers (e.g., filler 14A, filler 14B, filler 14C, and filler 14D) is formed. It should be noted that in this specification, "covering" refers to the situation in which the thin film 22 is in contact with the entire periphery of the filler cross section in the above cross-sectional photograph. In addition, the thin film 22 is not only sandwiched between the filler 14 and the resin 12, but is also sometimes sandwiched between the fillers 14.

[0059] <<<<Method for manufacturing structure>>>>

[0060] The method for producing the structured body of the present embodiment will be described in detail below. First, the raw materials used for producing the structured body of the present embodiment will be described, and then the method for producing the structured body of the present embodiment will be described.

[0061] <<<Insulator>>>

[0062] The insulator 10 of this embodiment is typically a cured product obtained by curing a curable composition containing various components described in detail below. The curable composition can be manufactured according to a known method, for example, by mixing, stirring and dispersing the components with a thermosetting resin, a photocurable resin, etc. as the main component. Hereinafter, the resin component, the filler and other components that are components of the curable composition of this embodiment will be described in detail.

[0063] <<Resin composition>>

[0064] The resin component of the present embodiment is not particularly limited, and in order to impart resistance to the gap forming process as a solidified material, a hydrophobic resin is preferably used. By increasing the hydrophobicity of the resin as the resin component, the insulator 10 becomes easy to fully have resistance to the gap forming process, and the penetration of the gap forming treatment liquid becomes easy to be suppressed. Therefore, during the gap forming process, the surface of the insulator 10 is easily suppressed from roughening. On the other hand, in addition to having low resistance to the gap forming process, the interface between the resin and the filler is also highly hydrophilic, so the gap forming treatment liquid is easy to penetrate, and roughening (porosity) is selectively easy to be carried out at the interface between the resin and the filler. Therefore, it is inferred that when the hydrophobicity of the resin is improved (for example, when a hydrophobic resin is used), a gap that is particularly suitable for the film formation of the present embodiment can be formed. As the resin component of the present embodiment, for example, polyester resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polyamide resins, polyamide-imide resins, polyphenylene sulfide resins, polyetheretherketone resins, polyethersulfone resins, polycarbonate resins, polyetherimide resins, epoxy resins, phenolic resins, phenoxy resins, glass-epoxy resins, polyphenylene ether resins (PPE), acrylic resins, silicone resins, polyolefin resins such as polyethylene and polypropylene, polycycloolefin resins such as polynorbornene, triazine resins such as melamine, etc. can be used. These resin components can be used alone or in combination of two or more. It should be noted that in this specification, the elastomer described later is not included in the "resin component".

[0065] As the preferred resin component of the present embodiment, for example, polyphenylene ether resin and epoxy resin can be cited. The main chain structure of the polyphenylene ether resin of the present embodiment can have a straight-chain structure (straight-chain polyphenylene ether resin), or can also have a branched structure (branched polyphenylene ether resin). In the case where the polyphenylene ether resin and other components are subjected to a curing reaction, it is preferred to have a functional group (also referred to as "containing unsaturated carbon bonds") containing unsaturated carbon bonds such as vinyl and allyl groups that do not damage dielectric properties, more preferably a hydrocarbon group containing unsaturated carbon bonds, particularly preferably a branched polyphenylene ether resin containing unsaturated carbon bonds, and especially more preferably a branched polyphenylene ether resin containing a hydrocarbon group containing unsaturated carbon bonds. The epoxy resin of the present embodiment is not particularly limited, and known conventional epoxy resins can be used.

[0066] The polyphenylene ether resin having a branched structure (also referred to as "branched polyphenylene ether resin") is a polyphenylene ether resin produced from a raw material phenol containing a phenol having hydrogen atoms at the ortho and para positions. Such phenols have hydrogen atoms at the ortho position, and therefore, when oxidatively polymerized with phenols, ether bonds can be formed not only at the ipso position and the para position, but also at the ortho position, so that the polyphenylene ether resin obtained by using the above phenols as raw material phenols can form a branched chain structure. Such branched polyphenylene ether resins are excellent in solubility in solvents, compatibility with each component in the composition, and reactivity.

[0067] Examples of the unsaturated carbon bond-containing polyphenylene ether resin having a branched structure include the polyphenylene ether resin disclosed in International Publication No. 2020 / 017570.

[0068] The polyphenylene ether resin containing unsaturated carbon bonds having a branched structure can be obtained by any of the following methods: (Method 1) a method of using phenols containing functional groups having unsaturated carbon bonds as raw material phenols to synthesize polyphenylene ether resins; or (Method 2) using phenols not containing functional groups having unsaturated carbon bonds as raw material phenols to synthesize polyphenylene ether resins, modifying the obtained polyphenylene ether resin, and introducing functional groups having unsaturated carbon bonds into the polyphenylene ether resin.

[0069] The unsaturated carbon bond-containing polyphenylene ether resin having a branched structure may be a mixture of two or more polyphenylene ether resins having different kinds of raw material phenols.

[0070] As other raw material phenols, for example, phenols represented by the following formula (1) can be used.

[0071]

[0072] In the above formula (1), R1 to R6 are each independently hydrogen or a hydrocarbon group having 1 to 10 carbon atoms.

[0073] Examples of the hydrocarbon group include an alkyl group, an alkenyl group, an alkynyl group, an aryl group, a cycloalkyl group, etc. When R1 to R6 are hydrocarbon groups, an alkyl group is preferred.

[0074] The phenol compound represented by the above formula (1) can be synthesized according to the following reaction formulas (A) to (C).

[0075]

[0076] In the above reaction formulae (A) to (C), R1 to R6 are each independently hydrogen or a hydrocarbon group having 1 to 10 carbon atoms. Examples of the hydrocarbon group include linear or branched alkyl groups.

[0077] The reaction shown in the reaction formula (A) is an addition reaction of the phenolic hydroxyl group of the raw material to the double bond of 3,4-dihydro-2H-pyran, more specifically, a tetrahydropyran protection reaction of the hydroxyl group. The reaction conditions can be appropriately selected from known conditions as the addition reaction of the double bond of the phenolic hydroxyl group. Specifically, as a reaction solvent, for example, dichloromethane can be cited. In addition, as a reaction catalyst, for example, pyridinium p-toluenesulfonate can be cited. The reaction shown in the reaction formula (A) can be carried out at room temperature.

[0078] The reaction shown in reaction formula (B) is a cross-coupling reaction of the compound shown in chemical formula (4) and chloromethylstyrene. The reaction conditions can be appropriately selected from known conditions as cross-coupling reactions. Specifically, for example, it can be carried out under a nitrogen atmosphere at 100°C. As a reaction solvent, for example, 2,4-dioxane, methanol, ethanol, toluene, tetrahydrofuran, dimethylformamide, water, etc. can be mentioned. In addition, as a base, sodium bicarbonate, sodium carbonate, potassium carbonate, sodium hydroxide, etc. can be mentioned. As a reaction catalyst, a palladium catalyst can be used, for example, tetrakis(triphenylphosphine)palladium can be mentioned.

[0079] The reaction shown in reaction formula (C) is a reaction for deprotecting the phenolic hydroxyl group of the compound shown in formula (3). The reaction conditions can be appropriately selected from known conditions for the deprotection reaction of the phenolic hydroxyl group. Specifically, for example, methanol can be mentioned as a reaction solvent. In addition, p-toluenesulfonic acid monohydrate can be mentioned as a reaction catalyst. The reaction shown in reaction formula (C) can be carried out at room temperature.

[0080] As other raw material phenols, phenols (X) represented by the following formula (11) can also be used.

[0081]

[0082] In formula (11), R A , R C , R E are each independently a functional group having 1 to 10 carbon atoms, R B , R D are each independently hydrogen or a functional group having 1 to 10 carbon atoms, R A ~R E At least one of them is a functional group containing an unsaturated carbon bond (preferably a functional group having 3 or more carbon atoms).

[0083] The phenol compound (X) may have only one functional group containing an unsaturated carbon bond, or may have two or more functional groups containing an unsaturated carbon bond.

[0084] In formula (11), R A , R C , R EPreferably, each independently is a hydrocarbon group having 10 or less carbon atoms, 5 or less carbon atoms, or 3 or less carbon atoms.

[0085] In formula (11), R B , R D Preferably, each independently represents hydrogen or a hydrocarbon group having 10 or less carbon atoms, hydrogen or a hydrocarbon group having 5 or less carbon atoms, hydrogen or a hydrocarbon group having 3 or less carbon atoms, hydrogen or a hydrocarbon group having 1 carbon atoms, or hydrogen.

[0086] As specific phenols (X), for example, a compound represented by the following formula (12) (4-allyl-2,6-dimethylphenol) or a compound represented by the following formula (13) (2-allyl-4,6-dimethylphenol) can be mentioned. Phenols (X) can be produced by a known method such as the synthesis method described in WO2021 / 070714.

[0087]

[0088] Examples of epoxy resins include bisphenol-type epoxy resins (bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, etc.), novolac-type epoxy resins (bisphenol A novolac-type epoxy resins, phenol novolac-type epoxy resins, cresol novolac-type epoxy resins, etc.), biphenyl-type epoxy resins, biphenyl novolac-type epoxy resins, and biphenyl aralkyl-type epoxy resins.

[0089] The curing agent of the epoxy resin is not particularly limited, and for example, active ester curing agents, phenol curing agents, acid anhydride curing agents, amine curing agents, imidazole curing agents, etc. can be used. From the viewpoint of improving the resistance to gap forming treatment by reducing the polar groups in the cured product and facilitating gap formation, it is preferred to use an active ester curing agent.

[0090] <<Packing>>

[0091] The material of the filler 14 of the present embodiment is not particularly limited as long as it is usually mixed in the insulating layer. In the case of making the structure 30 by the manufacturing method described later, it is preferred to have an acid-resistant and alkali-resistant material. As the material of the filler 14 of the present embodiment, an inorganic filler is preferred, and specifically, talc, mica, sericite, montmorillonite and other clay minerals, metal oxides such as silica, aluminum oxide, titanium oxide, aluminum hydroxide, magnesium hydroxide and other metal hydroxides, barium titanate, strontium titanate and other fillers with a perovskite-type crystal structure, boron nitride, aluminum borate, barium sulfate, calcium carbonate and the like can be cited. Among them, from the viewpoint of dielectric properties and thermal expansion, silica is preferred, and from the viewpoint of heat dissipation, aluminum oxide is preferred.

[0092] The average particle size of the filler of the present embodiment is preferably less than 1.0 μm, more preferably less than 0.8 μm, and further preferably less than 0.5 μm. It should be noted that, in this specification, "average particle size" refers to the median particle size (D50) measured by a laser diffraction particle size distribution meter. As a laser diffraction particle size distribution meter, for example, Microtrac MT3300EXII manufactured by MicrotracBEL Corp. can be used. In addition, the D90 of the filler of the present embodiment is preferably less than 2.0 μm, more preferably less than 1.5 μm, and further preferably less than 1.0 μm. It should be noted that, in this specification, "D50" and "D90" refer to the particle size at which the cumulative volume percentage of the particles measured in the same manner as above (the cumulative volume percentage in the volume particle size distribution when plotted from the side with a small particle size) becomes 50% and 90%. If the particle size of the filler is in such a range, a structure 10 with excellent adhesion can be obtained, and a high-precision conductor circuit pattern can be formed.

[0093] Regarding the filler 14 of the present embodiment, the presence or absence of surface treatment is not particularly limited, and a filler that has been surface treated to improve dispersibility and reactivity may also be used. As the surface treatment of the filler 14, surface treatment based on a coupling agent, surface treatment without introducing an organic group such as alumina treatment, etc. may be cited. As the coupling agent of the present embodiment, for example, a known silane coupling agent such as a vinyl silane coupling agent, a phenyl silane coupling agent, a phenyl amino silane coupling agent, a (meth) acrylic silane coupling agent, a styryl silane coupling agent, an epoxy silane coupling agent, a mercapto silane coupling agent, etc. may be used.

[0094] Examples of the vinylsilane coupling agent include vinyl alkoxysilanes such as vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, and vinyldimethylmethoxysilane.

[0095] Examples of the phenylsilane coupling agent include phenyltrimethoxysilane, phenyltriethoxysilane, and dimethoxydiphenylsilane.

[0096] Examples of the phenylaminosilane coupling agent include N-phenyl-3-aminopropyltrimethoxysilane and the like.

[0097] Examples of the (meth)acrylic silane coupling agent include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane.

[0098] Examples of the styrylsilane coupling agent include p-styryltrimethoxysilane and the like.

[0099] Examples of the epoxysilane coupling agent include 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropylmethyldimethoxysilane.

[0100] Examples of the mercaptosilane coupling agent include 3-mercaptopropyltriethoxysilane and the like.

[0101] As the method for treating the surface of the filler with a coupling agent, it is not particularly limited and known methods can be used. Usually, the alkoxy group of the coupling agent is hydrolyzed to generate a silanol group, the coupling agent is contacted with the filler, and the silanol group of the coupling agent is dehydrated and condensed with the hydroxyl group present on the filler surface, thus, the surface treatment of the filler can be carried out. This treatment can be implemented in a heated environment or a dry environment as required. In addition, the filler 14 of the present embodiment can use a commercially available product sold in a state of having been surface treated with a coupling agent.

[0102] For example, when the total mass of the filler is 100 parts by mass, the amount of the coupling agent used can be 0.1 to 5.0 parts by mass or 0.5 to 3.0 parts by mass.

[0103] The filler 14 of this embodiment can be mixed with other components in a powder or solid state according to the usage scheme, or can be mixed with a solvent or a dispersant to form a slurry and then mixed with other components. In order to improve the dispersibility of the filler 14, it is preferably mixed after forming a slurry. It should be noted that the mixing amount of the filler 14 described below refers to the value in the powder or solid state.

[0104] The amount of the filler 14 of the present embodiment is preferably 5% by volume or more and 50% by volume or less, more preferably 5% by volume or more and 30% by volume or less, further preferably 5% by volume or more and 25% by volume or less, and particularly preferably 5% by volume or more and 20% by volume or less relative to the total amount of the non-volatile components of the curable composition. When the amount of the filler 14 is within such a range, the adhesion between the insulator 10 and the conductor layer 20 is improved. In addition, by making the amount of the filler 14 less than 50% by volume, preferably less than 30% by volume, it is inferred that the distance between adjacent fillers 14 in the insulator 10 can be appropriately maintained, that is, the amount of the resin 12 existing between adjacent gaps formed in the gap forming process can be appropriately maintained. Therefore, the resin 12 around the filler 14 after the gap forming process also has sufficient strength, so it is believed that the gap can be suppressed from being destroyed and the filler 14 can be prevented from falling off from the insulator 10, and a gap particularly suitable for the film formation of the present embodiment can be easily formed.

[0105] <<Other additives>>

[0106] The curable composition of the present embodiment may contain other components as needed in addition to the above components within the range not impairing the effects of the present invention. Examples of the components that may be contained in the curable composition of the present embodiment include peroxides, crosslinking curing agents, elastomers, solvents, and the like.

[0107] In addition, other components may be known components such as sensitizers, adhesive aids, surfactants, leveling agents, plasticizers, adhesives, colorants, fibers, flame retardants, cellulose nanofibers, dispersants, curing catalysts, dispersion aids, thickeners, defoamers, antioxidants, rust inhibitors, and adhesiveness imparting agents.

[0108] <Peroxide>

[0109] In the curable composition of the present embodiment, when the resin component has a functional group containing an unsaturated carbon bond, it is preferred that the curable composition contain a peroxide.

[0110] Examples of the peroxide include methyl ethyl ketone peroxide, methyl acetoacetate peroxide, acetoacetyl peroxide, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, di-tert-butyl hydroperoxide, tert-butyl hydroperoxide, dicumyl peroxide, 2,5-dimethylhexane-2,5-dihydroperoxide, Methyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne, 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-butene, acetyl peroxide, octanoyl peroxide, lauroyl peroxide, benzoyl peroxide, m-toluoyl peroxide, diisopropyl peroxydicarbonate, tert-butyl peroxybenzoate, di-tert-butyl peroxide, tert-butyl peroxyisopropyl monocarbonate, α,α'-bis(tert-butylperoxy-m-isopropyl)benzene, etc. The peroxide may be used alone or in combination of two or more.

[0111] Among these, the peroxide is preferably one having a 1-minute half-life temperature of 130° C. to 180° C. from the viewpoint of ease of handling and reactivity. Such a peroxide has a high reaction starting temperature, and therefore, is less likely to promote curing at a time when curing is not required, such as during drying, and does not reduce the storage stability of the curable composition. In addition, since the volatility is low, it does not volatilize during drying and storage, and has good stability.

[0112] The amount of peroxide added is preferably 0.01 to 20 parts by mass, more preferably 0.05 to 10 parts by mass, and particularly preferably 0.1 to 10 parts by mass, based on the total amount of peroxide relative to 100 parts by mass of the solid content of the curable composition. By making the total amount of peroxide within this range, sufficient curability is obtained, and a cured product having excellent mechanical properties, heat resistance, dielectric properties, etc. can be obtained.

[0113] <Cross-linking curing agent>

[0114] The curable composition of the present embodiment preferably contains a cross-linking curing agent. The cross-linking curing agent is not particularly limited as long as it is a compound that undergoes a curing reaction with the resin 12 and is a commonly used cross-linking curing agent. As the cross-linking curing agent of the present embodiment, a curing agent with good compatibility with the resin component is preferably used.

[0115] The cross-linking curing agent of the present embodiment can include compounds with phenolic hydroxyl groups, polycarboxylic acids and their anhydrides, compounds with cyanate groups, alicyclic olefin polymers, multifunctional vinyl compounds, vinyl benzyl ether compounds, allyl ether compounds, triallyl isocyanurate, (meth) acrylate compounds, active ester compounds, etc. When polyphenylene ether resin is used as a resin component, the cross-linking curing agent of the present embodiment is preferably triallyl isocyanurate (hereinafter, TAIC (registered trademark)), triallyl cyanurate (hereinafter TAC). The cross-linking curing agent can be used alone or in combination of two or more.

[0116] In the curable resin composition, when a polyphenylene ether resin is used as a resin component, the mixing ratio of the polyphenylene ether resin to the cross-linking curing agent (e.g., trialenyl isocyanurate) is preferably 20:80 to 90:10, and more preferably 30:70 to 90:10, in terms of solid content ratio (resin component: cross-linking curing agent). By setting the ratio in such a range, a cured product 11 having low dielectric properties and excellent heat resistance can be obtained.

[0117] When epoxy resin is used as the resin component, the cross-linking curing agent of the present embodiment is preferably a compound having a phenolic hydroxyl group, an active ester compound. From the viewpoint of improving the resistance to gap formation processing and making the gap formation easy by reducing the amount of polar groups in the cured product, it is particularly preferred to use an active ester compound as a cross-linking curing agent. As an active ester compound, it is preferred to use a compound having more than two highly reactive ester groups in one molecule such as phenol esters, thiophenol esters, N-hydroxylamine esters, and esters of heterocyclic hydroxyl compounds. As a specific example of an active ester compound, an active ester compound comprising a dicyclopentadiene-type diphenol condensation structure, an active ester compound comprising a naphthalene structure, an active ester compound comprising an acetylated product of a phenol novolac, an active ester compound comprising a benzoylated product of a phenol novolac, etc.

[0118] In the curable resin composition, when an epoxy resin is used as the resin component, the blending ratio of the epoxy resin to the cross-linking curing agent (e.g., an active ester compound), for example, the epoxy group equivalent of the epoxy resin: the active ester group equivalent of the active ester compound, is preferably 80:20 to 50:50, more preferably 70:30 to 60:40.

[0119] <Elastomer>

[0120] The curable composition of the present embodiment may contain an elastomer. By containing an elastomer, the tensile properties of the cured product 11 are improved.

[0121] Elastomers are roughly divided into thermosetting elastomers and thermoplastic elastomers.

[0122] Examples of thermosetting elastomers include diene synthetic rubbers such as polyisoprene rubber, polybutadiene rubber, styrene-butadiene rubber, polychloroprene rubber, nitrile rubber, and ethylene-propylene rubber; non-diene synthetic rubbers such as ethylene-propylene rubber, butyl rubber, acrylic rubber, polyurethane rubber, fluororubber, silicone rubber, and epichlorohydrin rubber; and natural rubber.

[0123] Examples of the thermoplastic elastomer include styrene-based elastomers, olefin-based elastomers, urethane-based elastomers, polyester-based elastomers, polyamide-based elastomers, acrylic elastomers, and silicone-based elastomers.

[0124] When a polyphenylene ether resin is used as the resin component, the elastomer of this embodiment is preferably a styrene-butadiene copolymer such as a styrene-butadiene-styrene block copolymer; a styrene-isoprene copolymer such as a styrene-isoprene-styrene block copolymer; a styrene-ethylene-butylene-styrene block copolymer, a styrene-ethylene-propylene-styrene block copolymer, and the like, and hydrogenated products of these copolymers.

[0125] The weight average molecular weight of the elastomer of the present embodiment can be set to more than 1000 and less than 300000 or more than 2000 and less than 150000.It should be noted that, in this specification, the weight average molecular weight is measured by gel permeation chromatography (GPC), and is converted and obtained according to the standard curve made with standard polystyrene.If the weight average molecular weight is more than the aforementioned lower limit, the low thermal expansion is excellent, and if it is below the aforementioned upper limit, the compatibility with other components is excellent.

[0126] When the resin component is set to 100 parts by mass, the blending amount of the elastomer of the present embodiment can be set to 50 parts by mass or more and 200 parts by mass or less. Alternatively, the blending amount of the elastomer can be set to 5% by mass or more and 30% by mass or less based on the total solid content of the curable composition. When the elastomer is within such a range, good curability, formability, and chemical resistance can be achieved in a well-balanced manner.

[0127] <Solvent>

[0128] Curable composition is usually provided or used in the state that resin component is dissolved in solvent (solvent). As an example of solvent that can be used in the curable composition of the present embodiment, except the solvent that can be used in the past such as chloroform, dichloromethane, toluene, N-methyl-2-pyrrolidone (NMP), tetrahydrofuran (THF), cyclohexanone, propylene glycol monomethyl ether acetate (PMA), diethylene glycol monoethyl ether acetate (CA), methyl ethyl ketone, ethyl acetate and other safer solvents can also be cited. It should be noted that solvent can also be N, N-dimethylformamide (DMF). Solvent can use only 1 kind, or more than 2 kinds can be used.

[0129] The content of the solvent in the curable composition is not particularly limited and can be appropriately adjusted according to the application of the curable composition. The cured product 11 obtained by curing the curable composition usually does not contain a solvent.

[0130] <Ingredients that may become inappropriate>

[0131] In order to avoid increasing the surface roughness of the insulator surface after the gap forming treatment, the curable composition of the present embodiment preferably does not contain a component that has poor compatibility with the curable composition and dissolves in the gap forming treatment liquid (the alkali treatment liquid, oxidation treatment liquid, etc. described later). As components that may become inappropriate, for example, in the case of a curable composition containing a polyphenylene ether resin as a resin component, maleimide compounds having a long-chain aliphatic structure can be cited.

[0132] <Dry film>

[0133] The curable composition of the present embodiment can form a dry film. Specifically, at least one side of the resin layer formed by the curable composition of the present embodiment is supported or protected by a film. In addition, when the dry film of the present embodiment is made into a laminated body formed by two or more resin layers, it is sufficient as long as the resin layer having at least the surface on which the conductor layer is provided is a resin layer formed by the curable resin composition of the present embodiment.

[0134] The film (substrate film) serving as the support is not particularly limited, and may be a metal foil such as copper foil, a polyimide film, a polyester film, a polyethylene naphthalate (PEN) film, etc. It should be noted that these films may also be used as a support or a cover film of a dry film.

[0135] The dry film can be produced by, for example, applying a solution of the curable composition of the present embodiment onto a base film using an applicator or the like and drying to form a resin layer, and then laminating a cover film onto the resin layer as necessary.

[0136] The coating and drying during the manufacture of the dry film can be carried out according to known methods and conditions. For example, known coating methods such as a comma coater, a blade coater, a lip coater, a rod coater, a pressure coater, a reverse coater, a transfer roll coater, a gravure coater, and a spray coater can be used, and heating and drying can be carried out by known heating means such as a hot air circulation drying furnace, an IR furnace, a hot plate, and a conveyor furnace. In addition, the thickness of the resin layer can be adjusted by changing the coating conditions, the solid content of the curable composition, and the viscosity.

[0137] <<Conductor layer>>

[0138] The conductor layer 20 of this embodiment is formed of a conductor (metal). The type of conductor is not particularly limited to copper, silver, gold, tin, nickel, etc., and a combination of multiple types may be used. The type of conductor is typically copper or silver.

[0139] <<<<Manufacturing method>>>>

[0140] Hereinafter, an example of a method for manufacturing a structure according to the present embodiment will be described. Figure 2 The following is an overview of the process diagram.

[0141] <<<Preparation step of cured product 11>>>

[0142] First, if Figure 2 As shown in (a) of FIG. 1 , a cured product 11 is prepared by curing the curable composition.

[0143] The method for obtaining the cured product 11 from the curable composition is not particularly limited and can be appropriately changed according to the composition of the curable composition. As an example, after applying the curable composition to the substrate (e.g., by applying with an applicator, etc.), a drying process for drying the curable composition as required can be implemented, and a heat curing process for thermally crosslinking the resin 12 can be implemented by heating (e.g., heating based on an inert gas oven, a hot plate, a vacuum oven, a vacuum press, etc.). It should be noted that the conditions for implementation in each process (e.g., coating thickness, drying temperature and time, heating temperature and time, etc.) can be appropriately changed according to the composition, use, etc. of the curable composition. It should be noted that, as a substrate, in addition to printed wiring boards and flexible printed wiring boards with circuits pre-formed with copper or the like, copper-clad laminates of all grades (FR-4, etc.), as well as metal substrates, polyimide films, polyethylene terephthalate films, polyethylene naphthalate (PEN) films, glass substrates, ceramic substrates, wafer plates, etc. can also be cited. The copper-clad laminates use materials such as copper-clad laminates for high-frequency circuits using paper phenolic, paper epoxy, glass cloth epoxy, glass polyimide, glass cloth / non-woven epoxy, glass cloth / paper epoxy, synthetic fiber epoxy, fluororesin·polyethylene·polyphenylene ether, polyphenylene oxide (polyphenylene oxide)·cyanate ester, etc.

[0144] <<<Step of forming gap 13>>>

[0145] Then, if Figure 2 As shown in (b), a gap 13 is formed between the resin 12 and the filler 14 in the depth direction from the surface 17 of at least a portion of the cured product 11, thereby manufacturing an insulator 10. Such an insulator 10 can be obtained, for example, by subjecting the above-mentioned cured product 11 to a gap forming treatment. The cured product 11 of this embodiment is resistant to the gap forming treatment liquid, and therefore, the change in the surface roughness Ra before and after the gap forming treatment (before: cured product 11, after: insulator 10) is suppressed to an increase of 0 to 100 nm. For example, when the surface roughness Ra of the cured product 11 before the gap forming treatment is 40 nm, the surface roughness Ra of the insulator 10 after the gap forming treatment becomes less than 140 nm.

[0146] It should be noted that the gap forming process can be processed in the same manner as the roughening process for forming unevenness on the surface of the insulator to impart adhesion to the conductor layer, and the desmearing process for removing smear (residue) generated when forming a through hole by laser processing, etc. In other words, the roughening treatment liquid and the desmearing liquid can be used as the gap forming treatment liquid.

[0147] The gap forming treatment can be carried out, for example, by sequentially immersing in an alkaline treatment solution containing an aqueous solution of sodium hydroxide, an oxidizing treatment solution containing an aqueous solution of potassium permanganate or sodium permanganate and containing sodium hydroxide, and an acid treatment solution containing an aqueous solution of sulfuric acid. As commercially available alkaline treatment solutions, Swelling Dip Securiganth P (manufactured by Atotech Japan K.K.) can be cited, as oxidizing treatment solutions, Concentrate Compact CP (manufactured by Atotech Japan K.K.) can be cited, and as acid treatment solutions, Reduction Securiganth P500 (manufactured by Atotech Japan K.K.) can be cited. In the gap forming treatment, any treatment solution, whether the alkaline treatment solution or the oxidizing treatment solution, slightly dissolves the resin 12 on the surface 17 of the cured product 11, and further penetrates between the filler 14 and the resin 12, thereby forming a gap 13. It should be noted that the conditions for the gap forming treatment can be, for example, an alkaline treatment solution at 50 to 70°C for 0 to 10 minutes, an oxidizing treatment solution at 70 to 90°C for 5 to 20 minutes, or an acid treatment solution at 30 to 50°C for 5 minutes. By controlling the above conditions, the depth of the treatment liquid intrusion (i.e., the depth of the gap 13 formed) can be adjusted.

[0148] <<<Step of forming the conductor layer 20 >>>

[0149] Finally, if Figure 2 As shown in (c) and (d) of FIG. 1 , a conductor layer 20 is formed on at least a portion of the surface 17 of the insulator 10 to manufacture a structure 30. The conductor layer 20 can be typically formed as follows: a seed layer is formed by chemical plating, and then electrolytic plating is performed to form the structure 30. Specifically, palladium or the like, which serves as a catalyst for chemical plating, is adsorbed on the surface 17 and the gap 13 between the resin 12 and the filler 14. With the catalyst as a starting point, a chemical plating layer is precipitated, thereby forming a thin film 22 covering a plurality of fillers 14. Then, a conductive layer 20 is formed on the surface 17. Figure 2 Then, the chemical plating layer is used as a seed layer to form a first conductor layer 21 as shown in (c). Figure 2 A thicker second conductor layer 23 as shown in (d).

[0150] It should be noted that in this manual, for convenience, Figure 2 In the case where the first conductor layer 21 and the second conductor layer 23 in (d) are formed by chemical plating only without electrolytic plating, or the metal (e.g., copper) precipitated in chemical plating and electrolytic plating is the same, a Figure 1The conductor layer 20 and the thin film 22 are structured as shown in FIG30, which are formed of a single component. In addition, the conductors used in chemical plating and electrolytic plating may be different.

[0151] <<<Other optional processes>>>

[0152] After plating, a heat treatment called annealing may be performed at about 80 to 200° C. for about 10 to 100 minutes in order to remove stress in the metal and improve strength.

[0153] <<<<How to use the structure>>>>

[0154] The structure 30 of this embodiment can be used, for example, for wiring boards (e.g., multilayer printed wiring boards), processed products subjected to decorative plating, etc. Among them, it is suitable for forming high-precision circuits and wiring boards for forming high-frequency circuits. In addition, when the conductor circuit is formed by the conductor layer 20, patterning can be performed by a known method (e.g., a subtractive method, a semi-additive method).

[0155] The present invention is not limited to the above-described embodiments, and various modifications such as design changes may be added based on the knowledge of those skilled in the art. Such modified embodiments are also included in the protection scope of the present invention.

[0156] The structure 30 of the present embodiment may further stack other insulating layers on the opposite side of the interface 16 of the insulator 10. As other insulating layers, thermosetting compositions, photocurable compositions, cured products formed by curable compositions, thermoplastic compositions, etc. different from the insulator 10 may be used. As lamination methods, for example, the following methods may be cited: a method of forming the insulator 10 on a surface on which other insulating layers are formed; a method of separately preparing other insulating layers and cured products 11, and forming the insulator 10 after crimping them; a method of preparing by forming a multilayer dry film formed by the curable composition of the present embodiment and other curable compositions; etc. In this way, a layered structure in which other insulating layers are formed on the insulator 10 is also included in the protection scope of the present invention.

[0157] Example

[0158] Hereinafter, the present invention will be described in more detail using examples.

[0159] <<Raw Materials>>

[0160] The following materials were used as raw materials of the curable composition.

[0161] <Resin (A)>

[0162] A-1: Polyphenylene ether resin 1 (Synthesis Example 1)

[0163] A-2: Polyphenylene ether resin 2 (Synthesis Example 2)

[0164] A-3: Polyphenylene ether resin 3 (Synthesis Example 3)

[0165] A-4: Polyphenylene ether resin 4 (Synthesis Example 4)

[0166] A-5: Noryl SA9000 (manufactured by SABIC, methacrylic acid-modified linear polyphenylene ether)

[0167] A-6: OPE-2St-1200 (Mitsubishi Gas Chemical Co., Ltd., styrene-modified linear polyphenylene ether)

[0168] A-7: N-740 (manufactured by DIC Corporation, phenol novolac type epoxy resin)

[0169] A-8: ZX-1059 (manufactured by NIPPON STEEL Chemical & Material Co., Ltd., a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin)

[0170] A-9: NC-3000-H (manufactured by Nippon Kayaku Co., Ltd., biphenyl aralkyl type epoxy resin)

[0171] A-10: JER828 (manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy resin)

[0172] A-11: YX6954BH30 (Mitsubishi Chemical Corporation, phenoxy resin)

[0173] <Padding (B)>

[0174] B-1: YA050C-HHL (manufactured by Admatechs, spherical silica, average particle size 0.05 μm, vinyl silane treatment, cyclohexanone slurry, non-volatile content 40%)

[0175] B-2: Sciqas (manufactured by Sakai Chemical Industry Co., Ltd., spherical silica, average particle size 0.05 μm, phenylsilane treated, non-volatile 100%)

[0176] B-3: 3SV-CH3 (manufactured by Admatechs, spherical silica, average particle size 0.3 μm, vinyl silane treated, cyclohexanone slurry, non-volatile content 60%)

[0177] B-4: 3SX-CH1 (manufactured by Admatechs, spherical silica, average particle size 0.3 μm, phenylaminosilane treated, cyclohexanone slurry, non-volatile content 60%)

[0178] B-5: 3SQ-CH1 (manufactured by Admatechs, spherical silica, average particle size 0.3 μm, no surface treatment, cyclohexanone slurry, non-volatile content 60%)

[0179] B-6: SC2050-HNF (manufactured by Admatechs, spherical silica, average particle size 0.5 μm, vinyl silane treated, cyclohexanone slurry, non-volatile content 70%)

[0180] B-7: 5SP-CH1 (manufactured by Admatechs, spherical silica, average particle size 0.5 μm, phenylsilane treated, cyclohexanone slurry, non-volatile content 70%)

[0181] B-8: 5SX-CH3 (manufactured by Admatechs, spherical silica, average particle size 0.5 μm, phenylaminosilane treated, cyclohexanone slurry, non-volatile content 70%)

[0182] B-9: 5SQ-CH1 (manufactured by Admatechs, spherical silica, average particle size 0.5 μm, no surface treatment, cyclohexanone slurry, non-volatile content 70%)

[0183] <Peroxide (C)>

[0184] C-1: PERBUTYL (registered trademark) P40 (manufactured by NOF Corporation, α,α'-bis(tert-butylperoxy-m-isopropyl)benzene)

[0185] <Cross-linking curing agent (D)>

[0186] D-1: TAIC (registered trademark) (manufactured by Mitsubishi Chemical Corporation)

[0187] D-2: EPICLON (registered trademark) HPC-8000-65T (manufactured by DIC Corporation)

[0188] D-3: LA-3018 (made by DIC Co., Ltd.)

[0189] <Elastomer (E)>

[0190] E-1: Tuftec (registered trademark) H1051 (manufactured by Asahi Kasei Corporation, hydrogenated styrene-based thermoplastic elastomer)

[0191] <Additives (F)>

[0192] F-1: BYK (registered trademark)-1791 (manufactured by BYK Japan Co., Ltd., surfactant)

[0193] F-2: BYK (registered trademark)-352 (manufactured by BYK Japan Co., Ltd., surfactant)

[0194] F-3: POLYFLOW No.90 (manufactured by Kyoeisha Chemical Co., Ltd., surfactant)

[0195] F-4: DMAP (dimethylaminopyridine, curing catalyst)

[0196] F-5: KBM-403 (manufactured by Shin-Etsu Silicone Co., Ltd., dispersion aid)

[0197] <Solvent>

[0198] Cyclohexanone

[0199] <<Manufacturing method>>

[0200] <Manufacturing of polyphenylene ether resin>

[0201] The polyphenylene ether resin is produced according to the method disclosed in International Publication No. 2020 / 017570. Specifically, it is as follows.

[0202] <Synthesis example 1>

[0203] In a 3L two-necked eggplant flask, 2.6g of diμ-hydroxy-bis[(N,N,N',N'-tetramethylethylenediamine)copper(II)] chloride (Cu / TMEDA) and 3.18mL of tetramethylethylenediamine (TMEDA) were added and fully dissolved, and oxygen was supplied at 10ml / min. 105g of 2,6-dimethylphenol and 13g of 2-allylphenol as raw material phenols were dissolved in 1.5L of toluene to prepare a raw material solution. The raw material solution was added dropwise to the flask, and the mixture was reacted at 40°C for 6 hours while stirring at a speed of 600rpm. After the reaction was completed, the mixture was reprecipitated with a mixed solution of 20L of methanol and 22mL of concentrated hydrochloric acid, filtered out, and dried at 80°C for 24 hours to obtain a polyphenylene ether resin 1 having a functional group with an unsaturated carbon bond and a branched structure. The number average molecular weight of the polyphenylene ether resin 1 was 13500 and the weight average molecular weight was 50000.

[0204] <Synthesis example 2>

[0205] In a 100 mL two-necked eggplant flask, 2.34 g of 2,6-dimethylphenol, 0.342 g of 2-allylphenol, 0.382 g of 2-allyl-4,6-dimethylphenol and 17.7 g of toluene were added as raw material phenols and stirred to completely dissolve. 0.065 g of di-μ-hydroxy-bis[(N,N,N',N'-tetramethylethylenediamine)copper(II)] chloride (Cu / TMEDA) and 0.076 g of tetramethylethylenediamine (TMEDA) were added to the adjusted raw material solution, and dry air was supplied at 10 ml / min. The mixture was reacted at 40°C for 15 hours while stirring at a rotation speed of 350 rpm. After the reaction, the mixture was reprecipitated with a mixture of 600 mL of methanol, 5 mL of ion exchange water, and 1 mL of concentrated hydrochloric acid, filtered out, and dried at 80° C. for 4 hours to obtain a polyphenylene ether resin 2 having a functional group with an unsaturated carbon bond and a branched structure. The number average molecular weight of the polyphenylene ether resin 2 was 12,700 and the weight average molecular weight was 33,200.

[0206] <Synthesis example 3>

[0207] In a 100 mL two-necked eggplant flask, 7.44 g of 2,6-dimethylphenol, 0.930 g of 2-allylphenol, 1.03 g of 4-allyl-2,6-dimethylphenol and 52.39 g of toluene were added as raw material phenols and stirred to completely dissolve. 0.206 g of di-μ-hydroxy-bis[(N,N,N',N'-tetramethylethylenediamine)copper(II)] chloride (Cu / TMEDA) and 0.195 g of tetramethylethylenediamine (TMEDA) were added to the adjusted raw material solution, and dry air was supplied at 30 ml / min. The mixture was reacted at 40°C for 23 hours while stirring at a rotation speed of 350 rpm. After the reaction, the mixture was reprecipitated with a mixture of 500 mL of methanol: 10 mL of ion exchange water: 1 mL of concentrated hydrochloric acid, filtered out, and dried at 80° C. for 4 hours to obtain a polyphenylene ether resin 3 having a functional group with an unsaturated carbon bond and a branched structure. The number average molecular weight of the polyphenylene ether resin 3 was 14,600 and the weight average molecular weight was 92,900.

[0208] <Synthesis example 4>

[0209] In a 100 mL two-necked eggplant flask, 3.61 g of 2,6-dimethylphenol, 0.507 g of 2-allylphenol, 0.882 g of 2,6-dimethyl-4-(4-vinylbenzyl)phenol and 28.91 g of toluene were added as raw material phenols and stirred to completely dissolve. 0.119 g of di-μ-hydroxy-bis[(N,N,N',N'-tetramethylethylenediamine)copper(II)] chloride (Cu / TMEDA) and 0.131 g of tetramethylethylenediamine (TMEDA) were added to the adjusted raw material solution, and dry air was supplied at 17 ml / min. The mixture was reacted at 40°C for 15 hours while stirring at a rotation speed of 350 rpm. After the reaction, the mixture was reprecipitated with a mixture of 500 mL of methanol: 5 mL of ion exchange water: 1 mL of concentrated hydrochloric acid, filtered out, and dried at 80° C. for 3 hours to obtain a polyphenylene ether resin 2 having a functional group with an unsaturated carbon bond and a branched structure. The number average molecular weight of the polyphenylene ether resin 4 was 12,700 and the weight average molecular weight was 45,300.

[0210] <Preparation of curable composition>

[0211] The curable compositions of the embodiments and comparative examples were prepared as follows: the above raw materials were mixed in the amounts shown in Table 1-1, Table 1-2 and Table 2, and fully stirred and mixed with a rotation / revolution mixer to prepare. It should be noted that the amounts shown in Table 1-1, Table 1-2 and Table 2 represent the amounts based on the components (solid content) other than the volatile components.

[0212] <Curing process>

[0213] Each curable composition was applied on a PET film using an applicator so that the theoretical film thickness after curing was 40 μm, and dried in a drying oven at 90° C. for 10 minutes to prepare a dry film having a resin layer derived from each curable composition. Next, each dry film was laminated on a copper-clad laminate at 100° C. and 0.5 MPa in a vacuum laminator, and after peeling off the PET film, it was heated at 200° C. for 60 minutes in an inert gas oven to prepare a test substrate having a cured product derived from each curable composition.

[0214] <Gap Forming Process>

[0215] The following commercially available gap forming treatment liquid was used to perform gap forming treatment on the surface of the cured product of each test substrate to obtain the insulator of the present embodiment. Specifically, as the alkaline treatment liquid, Swelling Dip Security P (manufactured by Atotech Japan KK) was used, as the oxidation treatment liquid, Concentrate Compact CP (manufactured by Atotech Japan KK) was used, and as the acid treatment liquid, Reduction Security P500 (manufactured by Atotech Japan KK) was used, and the treatment was performed at the liquid temperature and immersion time described in Table 1-1, Table 1-2, and Table 2.

[0216] <Conductor layer forming step>

[0217] Chemical plating and electrolytic plating were performed on each insulator to form a conductor layer and obtain a structure. Specifically, as a chemical plating treatment, the insulator was immersed in a cleaning treatment solution (Cleaner MCD-PL, manufactured by Uemura Industry Co., Ltd.) at 40°C for 5 minutes, immersed in a soft etching treatment solution (ALCUP (registered trademark) Preci-Dip MDP-2, manufactured by Uemura Industry Co., Ltd.) at 25°C for 2 minutes, immersed in a catalyst imparting treatment solution (ALCUP (registered trademark) MAT-SP, manufactured by Uemura Industry Co., Ltd.) at 40°C for 5 minutes, immersed in a reducing treatment solution (ALCUP (registered trademark) Reducer MRD-2-C / MAB-4-C / MAB-4-A, manufactured by Uemura Industry Co., Ltd.) at 35°C for 3 minutes, immersed in a reactive accelerating treatment solution (ALCUP (registered trademark) Accelerator The surface of the substrate was immersed in an electroless plating solution (MEL-3-A, manufactured by Uemura Industry Co., Ltd.) for 1 minute, and immersed in an electroless plating solution (THRU-CUP (registered trademark) PEA V2 manufactured by Uemura Industry Co., Ltd.) for 20 minutes at 36°C to perform electroless copper plating. Thereafter, as an electrolytic plating treatment, it was immersed in an acid cleaning solution (Atotech Japan KK manufactured, acid cleaning solution) at 46°C for 5 minutes, immersed in a 10% sulfuric acid aqueous solution at 25°C for 1 minute, immersed in a copper sulfate plating solution at 25°C for 60 minutes, and electrolytic copper plating was performed under the condition of a current density of 2A / 2dm. Finally, as annealing, a heat treatment was performed at 190°C for 60 minutes using a hot air circulation drying furnace.

[0218] <<Evaluation>>

[0219] The following evaluations were performed on each of the Examples and Comparative Examples. The results are shown in Table 1-1, Table 1-2, and Table 2. It should be noted that Example 3 and Example 10 in Table 2 are repeated records of Table 1-1 and Table 1-2. The details of each evaluation method are described below.

[0220] <Depth from interface>

[0221] For each structure (cross section), a Schottky scanning electron microscope (manufactured by Hitachi High-Tech Corporation) was used to photograph Examples 1 to 5, Examples 13 to 17, and Comparative Example 3 at 10,000 to 50,000 times, Examples 6 to 8 at 5,000 to 10,000 times, Examples 9 to 12, Examples 18 to 22, Comparative Example 2, and Comparative Example 4 at 5,000 to 10,000 times, and the longest depth of the conductor layer component penetrating between the filler and the resin of the insulator was measured at five points in the vertical direction from the interface where the insulator and the conductor layer contact toward the insulator, and the average value was calculated. Figure 3 The structure of Example 3 is shown in FIG. Figure 4 The structure of Example 6 is shown in Figure 5 , an enlarged image of a cross-sectional photograph of the structure of Comparative Example 2 is shown. In each enlarged image, the white-looking portion represents the conductor layer and its components, the gray-looking portion represents the filler (silicon dioxide), and the black-looking portion represents the resin. In this way, in the embodiment, the component forming the conductor layer enters between a portion of the filler and the resin and is connected to the conductor layer.

[0222] It should be noted that for each Example and each Comparative Example, it was confirmed whether a gap was formed between the filler and the resin. The confirmation results are shown in Table 1-1, Table 1-2, and Table 2. The case where a gap was formed was recorded as "yes", and the case where no gap was formed was recorded as "no".

[0223] <Plating expansion>

[0224] For each structure, the state of the copper plating layer (conductor layer) of each sample was observed, and the plating expansion was evaluated. The evaluation criteria are as follows.

[0225] None: There is neither expansion nor peeling in the copper plating layer (conductor layer)

[0226] Yes: Swelling or peeling is visible in the copper plating layer (conductor layer)

[0227] <Surface roughness Ra>

[0228] For each insulator before the conductor layer forming step, the arithmetic mean surface roughness was measured for any 10 locations on the surface where the conductor layer was formed using a white interference microscope (Bruker Contour GT-I, manufactured by Bruker Japan Co., Ltd., with a measurement range of 0.17 mm × 0.13 mm) corresponding to the non-contact measurement method. The average value of each measured value was taken as the surface roughness Ra of the insulator. In addition, Examples 3, 10, and 13 to 22, and Comparative Examples 3 and 4 are as follows: For each insulator after each structure was immersed in a 25°C ferric chloride solution until the conductor layer was completely removed, the surface roughness Ra was also measured in the same manner.

[0229] <Peel strength>

[0230] For each structure, the peel strength was evaluated. Specifically, first, a 10 mm wide and 60 mm long incision was introduced into the conductor layer of each sample. While peeling off one end of the length direction of the conductor layer in the region where the incision was introduced, the peeling position was clamped with a gripper, and a desktop tensile tester (EZ-SX made by Shimadzu Corporation) was used to peel off the copper plating layer (conductor layer) only 35 mm in length at an angle of 90 degrees and at a speed of 50 mm / minute, and the peel strength (N / cm) was measured. It should be noted that in Comparative Example 1, the coating expanded at the moment after the annealing process, so the peel strength could not be measured.

[0231] [Table 1-1]

[0232]

[0233] [Table 1-2]

[0234]

[0235] [Table 2]

[0236]

[0237] Description of Reference Numerals

[0238] 10 Insulator

[0239] 11 cured product

[0240] 12 Resin

[0241] 13 Gap

[0242] 14 Filling

[0243] 16 Interface

[0244] 17 Surface

[0245] 20 Conductor layer

[0246] 211st conductor layer

[0247] 22 films

[0248] 23 2nd conductor layer

[0249] 30 Structure

Claims

1. A structure, characterized in that: have: Insulators, and a conductive layer provided on at least a portion of the surface of the insulator, The insulator comprises a resin and a filler, The conductive layer component which is the same as at least one component constituting the conductive layer enters from the interface between the insulator and the conductive layer into between a part of the filler and the resin, and is connected to the conductive layer.

2. The structure according to claim 1, wherein The conductive layer component that enters between the filler and the resin forms a thin film covering the plurality of fillers.

3. The structure according to claim 1 or 2, wherein: The average particle size of the filler is 1.0 μm or less.

4. The structure according to claim 1 or 2, wherein: The depth of the conductive layer component that has penetrated between the filler and the resin from the interface is 1.5 times or more and 22 times or less the average particle size of the filler.

5. The structure according to claim 1 or 2, wherein: The filler is a metal oxide.

6. The structure according to claim 1 or 2, wherein: The component is a metal component.

7. A wiring board comprising the structure according to claim 1 or 2.

Citation Information

Patent Citations

  • Thermosetting resin composition, multilayered printed wiring board, and preparation thereof

    JP1995304931A

  • Curable resin composition, multilayered printed wiring board using the same, and manufacture thereof

    JP1995304933A

  • Inter-layer adhesive film for multilayered printed wiring board and multilayered printed wiring board using the same

    JP1999087927A

  • Poly(phenylene ether), curable composition containing poly(phenylene ether), dry film, prepreg, cured object, laminate, and electronic component

    WO2020017570A1

  • Liquid crystal alignment agent, liquid crystal alignment film, and liquid crystal display element

    WO2021070714A1